Comparative Validity of LEA Contrast Sensitivity Chart to Pelli-Robson Contrast Sensitivity Chart in Neuroophthalmology Patients: Oral Presentation - Observational Study - Resident - Lovenia Valencia; Riski Prihatningtias (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : The Pelli-Robson and LEA contrast sensitivity chart are widely used to measure clinical contrast sensitivity. The Pelli-Robson is a gold standard with the limitation of its bulky size. The LEA contrast sensitivity chart offers a reliable test in a way more practical and portable chart. This condition led to a question of whether we can predict Pelli-Robson score based on the LEA score. This study developed a conversion method to facilitate the transition from the LEA to the Pelli-Robson and validating the conversion score. Methods : This study retrospectively examined the relationship between LEA and Pelli-Robson Contrast Sensitivity Test. There were 120 eyes included in this study. We produced a conversion table using the equipercentile equating method. Then, we evaluated the reliability and accuracy of this algorithm to convert the LEA to the Pelli-Robson contrast sensitivity score. Results : LEA scores were converted to Pelli-Robson scores according to a conversion table that achieved a reliability of 0.91 based on intraclass correlation. The accuracy of this algorithm was 81.6% within 1 point difference from the raw score. Conclusion : This study reported a reliable and comparable conversion algorithm for transforming LEA scores into converted estimated Pelli-Robson scores. This method will enhance the utility of existing data in clinical and research settings.